Analytical modeling and experimental verification for linearly gradient thickness disk springs. (October 2021) - Du, Xinxin; Liao, Changrong; Gan, Bin; Zhang, Yonghao; Xie, Lei; Zhang, Honghui
Abstract: Even though disk springs with non-uniform thickness have the advantages of improving the load capacity, optimizing the stress distribution, and adjusting the stiffness characteristics, their exploration remains sparse. Prior analytical models for non-uniform disk springs were based on the Almen–Laszlo theory, and the model verifications lacked the support of experiments. A mechanical model of linearly gradient thickness (LGT) disk springs is established in this study in the cylindrical coordinate system based on the theory of plates and shells. A new analytical equation as a function of material and geometric parameters is developed to describe the load–deflection characteristics of LGT disk springs. The load–deflection characteristics of disk springs with different thickness variation parameters are compared through cases with a constant mid-radius thickness and constant flattened load, respectively. Moreover, the stiffness, deformation energy, and stress distribution of the disk springs are also systematically analyzed. To verify the proposed model and characterize the nonlinear load–deflection properties of LGT disk springs, specimens were fabricated, and experimental tests were conducted. Comparisons between the analytical results and experimental data demonstrate the superior effectiveness and accuracy of the developed analytical model in predicting the load–deflection characteristics of disk springs with uniform thickness or LGT. The results from the analytical and finite element methods indicate that the proposed model can describe the load–deflection characteristics of disk springs with different cone angles. Highlights: A novel analytical model for disk springs with linearly gradient thickness is developed. The influences of thickness variation on mechanical properties are systematically investigated. Experiments on load-deflection relationships are conducted, and the validity of the proposed model is verified.